HEALTHY EATING AND ITS IMPACT ON HEALTH - Bozorova Jonona Dilovarovna; Nuritdinova Parvina Sharofitdinovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article discusses the impact of a healthy diet on the overall health of a person, based on data from numerous scientific studies. A healthy diet is defined as a balanced diet rich in macronutrients and micronutrients that includes fruits, vegetables, whole grains and lean proteins. The article demonstrates that following the principles of a healthy diet can significantly reduce the risk of cardiovascular disease, metabolic disorders and certain cancers, as well as having a positive impact on mental health. The statistical evidence presented, such as the results of the INTERHEART and EPIC studies, supports the importance of good nutrition in preventing disease and improving quality of life. In conclusion, the need for further research on the impact of nutrition on health is emphasized in order to formulate effective public health strategies and increase public awareness of the importance of a healthy diet.